Helicoverpa genus on the edge of the continental U.S.: Flight phenology, analysis of hybrid presence, and insecticide performance in high-input field crops in Puerto Rico - Flores-Rivera, Xiomara L.; Paula-Moraes, Silvana V.; Johnson, James W.; Jack, Cameron J.; Perera, Omaththage P. (Frontiers in Insect Science, 2022)
The genus Helicoverpa includes several agricultural pests globally. Helicoverpa armigera was reported in several countries in South America in 2013, and in Puerto Rico, in 2014. This territory is considered an agricultural hub, with a high-input system of seed production in the southern region of the island, and also at the edge of the continental U.S. Possible natural dispersion of populations of H. armigera from the Caribbean or other Central American regions poses a continuing risk to the U.S. This study was performed during the post-detection scenario of H. armigera in Puerto Rico, from 2018 to 2021. A year-round pheromone trapping program of adult males indicated an increase in the population from October to March and differences in the occurrence of Helicoverpa spp. between the municipalities Juan Diaz and Salinas. The proportion of H. armigera/H. zea and detection of congeneric hybrids between these species were assessed based on genital morphology and DNA analysis. Interestingly, neither H. armigera nor expected hybrids were detected in the present study. The susceptibility of H. zea populations to the insecticides Spinetoram, Emamectin benzoate, Chlorantraniliprole, and Esfenvalerate was assessed, and an overall significant effect of insecticide susceptibility was detected. Chlorantraniliprole and Emamectin benzoate had the highest efficacy. These results contribute to the Integrated Pest Management and Insect resistance management programs to Helicoverpa spp. in Puerto Rico. In addition, provide validated information to be considered in mitigation plans, in the scenario of an invasion of H. armigera in the continental U.S.